The Effect of Human Resource Quality and Competitiveness on Cooperative Organization Performance - Abdul Kadir; Fredy Jayen; Rifqi Amrulloh (Universitas Negeri Semarang, 2023)
An organizational leader must have the right decision-making ability so that the goals and objectives of the organization that have been set can be achieved. The achievement of organizational goals and objectives is one proof that organizational performance is good. Organizational performance is measured by financial and non-financial performance parameters. Effective organizational performance will help the organization gain a substantial competitive advantage. A cooperative is a non-profit organization that provides services to its members just like a bank. The performance of cooperative organizations is not only focused on financial performance, because in its operations cooperatives carry out social values. This study aims to determine the effect of Human Resource Quality and Competitiveness on Organizational Performance in Cooperative X. This research method uses an associative research approach with sampling carried out using unsaturated sampling techniques. The number of samples is equal to the total population of 21 people. Primary data were collected using the help of research instruments in the form of questionnaires with assessment intervals of 1-4. The independent variable in the study is represented by the quality of human resources (X1) and competitiveness (X2), while the dependent variable is represented by organizational performance (Y). The results showed that the research data were normally distributed because L count from L table (0.0929 0.1953) with a confidence level of 0.05. The quality of human resources significantly affects organizational performance in Cooperative X as evidenced by a signification value of 0.047 0.05; while competitiveness has an insignificant influence on organizational performance as evidenced by a signification value of 9.692 0.05. Multiple linear equations are formulated . Based on simultaneous tests, it was obtained that the null hypothesis was accepted as evidenced by a signification value of 0.0478 0.05. This means that the variables of human resource quality and competitiveness simultaneously have a significant effect on organizational performance in Cooperative X.